Ego depletion and attention regulation under pressure: is a temporary loss of self-control strength indeed related to impaired attention regulation? - Englert, Christoph; Zwemmer, Kris; Bertrams, Alex; Oudejans, Raôul R. D. (Journal of sport & exercise psychology, 2015)
In the current study we investigated whether ego depletion negatively affects attention regulation under pressure in sports by assessing participants' dart throwing performance and accompanying gaze behavior. According to the strength model of self-control, the most important aspect of self-control is attention regulation. Because higher levels of state anxiety are associated with impaired attention regulation, we chose a mixed design with ego depletion (yes vs. no) as between-subjects and anxiety level (high vs. low) as within-subjects factor. Participants performed a perceptual-motor task requiring selective attention, namely, dart throwing. In line with our expectations, depleted participants in the high-anxiety condition performed worse and displayed a shorter final fixation on bull's eye, demonstrating that when one's self-control strength is depleted, attention regulation under pressure cannot be maintained. This is the first study that directly supports the general assumption that ego depletion is a major factor in influencing attention regulation under pressure